2021
DOI: 10.1021/acs.jpca.1c02032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligand Modulation on Metal-to-Metal Electron Transfer in a Series of [Fe2Co2] Molecular Square Complexes

Abstract: A series of three new cyanide-bridged [FeCo] molecular square complexes, namely, {[Fe(Tp*)(CN) 3 ] 2 [Co-(L) 2 ] 2 }(BF 4 ) 2 •2DMF (L = bik (1), bik* (2), and vbik (3); Tp* = hydrotris(3,5-dimethylpyrazol-1-yl)borate, bik = bis(1-methyl-1H-imidazol-2-yl)ketone, bik* = bis(1-ethyl-1H-imidazol-2-yl)ketone, and vbik = bis(1-vinyl-1H-imidazol-2-yl)ketone; DMF = dimethylformamide) were synthesized and characterized by singlecrystal X-ray diffraction analyses and by magnetic, electrochemical, and spectroscopic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…18 In 2004, K. Dunbar et al reported a molecular trigonal pyramidal [Co 3 Fe 2 ] complex and its thermally induced ETCST at the molecular level for the first time. 19 Up to now, cyanide-bridged molecular complexes with [CoFe], 20 [CoFe 2 ], 21–23 [Co 2 Fe 2 ], 24–32 [Co 3 Fe 2 ], 19,33,34 [Co 4 Fe 4 ], 35 [Co 5 Fe 4 ], 36 and [Co 6 Fe 4 ] 37 cores were reported to show ETCST upon temperature changes and light irradiation in solids. Since thermal ETCST is an intramolecular redox process, the redox potentials of the donor and acceptor sites are important for designing molecular ETCST complexes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 In 2004, K. Dunbar et al reported a molecular trigonal pyramidal [Co 3 Fe 2 ] complex and its thermally induced ETCST at the molecular level for the first time. 19 Up to now, cyanide-bridged molecular complexes with [CoFe], 20 [CoFe 2 ], 21–23 [Co 2 Fe 2 ], 24–32 [Co 3 Fe 2 ], 19,33,34 [Co 4 Fe 4 ], 35 [Co 5 Fe 4 ], 36 and [Co 6 Fe 4 ] 37 cores were reported to show ETCST upon temperature changes and light irradiation in solids. Since thermal ETCST is an intramolecular redox process, the redox potentials of the donor and acceptor sites are important for designing molecular ETCST complexes.…”
Section: Introductionmentioning
confidence: 99%
“…29 Mondal and co-workers reported that in their [Co 2 Fe 2 ] squares, changing the capping ligands on the Co sites caused different crystal packings and bistable behavior. 30 The ETCST behavior in solid is also influenced by intermolecular interactions. For example, Liu and co-workers reported a series of {[Fe(PzTp)(CN) 3 ] 2 [Co(dpq) 2 ] 2 }X 2 (PzTp − = tetrakis(pyrazolyl)borate, dpq = dipyrido[3,2- d :2′,3′- f ]quinoxaline, and X = BF 4 − , PF 6 − , and OTf − ) that have different intermolecular interactions, leading to quite different ETCST behavior and T 1/2 values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 These materials have shown significant importance in a broad area of quantum science and technology. [3][4][5] Spin manipulation in bistable materials with spin crossover (SCO), [6][7][8][9][10][11][12][13][14][15] singlemolecule magnet (SMM), [16][17][18][19][20][21][22] single-chain magnets (SCM) [23][24][25] and metal-to-metal electron transfer [26][27][28][29][30][31][32] properties has been well investigated for decades, where SCO molecules represent the most important and exciting materials [33][34][35] due to their easy manipulation for application. [36][37][38][39][40] Various external stimuli, including temperature, light, and pressure, have been applied to tune their bistability precisely with significant alteration in photophysical properties (magnetic, conductive, optical, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the molecular systems that can allow access to room temperature bistability and photomagnetic effects are the most fascinating. Over the last few decades, the switchable magnetic materials based on transition metals are gaining momentum with effective importance, particularly materials showing photo-, magnetic, or electric bistabilities such as spin crossover (SCO), single-molecule magnets (SMMs), single-chain magnets (SCMs), metal-to-metal electron transfer (MMET), etc . Especially, SCO materials represent a prominent field to provide an attractive and potential way to attain molecular spintronic, molecular sensors, and nanoscale devices over the past few decades. In the SCO phenomenon, the spin states of the 3d transition-metal complexes with d 4 -d 7 electronic configuration in octahedral geometry can be reversibly switched between low-spin (LS) and high-spin (HS), which has been well known for almost nine decades and remains one of the most interesting electronic dynamics in coordination chemistry. , The spin-state switching can be originated by modification of external perturbation, e.g ., temperature, pressure, light irradiation, magnetic field, etc ., and is often accompanied by a physical change in color, volume, and in magnetic, conductive, optical, and other physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%